Narrative Approach To Living Heritage - Walter, Nigel (Protection of Cultural Heritage, 2020)
This paper attempts to sketch out a theoretical framework that addresses the particular needs of living heritage. ICCROM has been at the forefront of developing a conservation practice which addresses the concerns of living heritage such as religious and pilgrimage sites (e.g. Wijesuriya 2015; Wijesuriya, Thompson, and Court 2017), and others have considered the implications for the conservation process (e.g. Poulios 2014). However, to date there has been no attempt to develop a theoretical foundation for these practices. In place of the still-dominant understanding (at least as encountered in much Western practice) of historic buildings as primarily art-historical, this paper proposes a narrative approach that allows the site or building to remain within its cultural/religious context, including an acceptance of ongoing change. While the argument proceeds from Western sources, it invites dialogue with complementary understandings of the working of tradition from other regions of the world. Any theoretical model for living heritage must address the central question of how living buildings endure between generations, that is, their continuity between past, present and future. Since modernity entails a commitment to a radical discontinuity with the past, such an approach must engage with the resources of premodernity to develop (or perhaps return to) a non-modern understanding of tradition as developmental and creative (Author, 2017). The principal sources used in the investigation of this proposed narrative approach include Alasdair MacIntyre’s rehabilitation of tradition, Hans-Georg Gadamer’s development of philosophical hermeneutics and Paul Ricoeur’s work on narrative and time.